KAJIAN LITERATUR : ANALISIS EFEKTIVITAS PENGGUNAAN MULTIMEDIA DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Widia Putri Febriani; Nabila Sasgita; Rica Syofiana Sari; Tiara Ananda (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
Science learning faces various challenges due to abstract concepts that are difficult for students to understand. Therefore, an innovative solution to address these challenges is the use of multimedia in science learning. The purpose of this study was to analyze the effectiveness of multimedia use in science learning in elementary schools. The method used was a literature review of 12 articles published between 2020 and 2025. The analysis showed that multimedia, such as animation, interactive videos, and simulation videos, have proven effective in explaining abstract science concepts concretely and attracting students' interest, motivation, and activeness, thereby improving conceptual understanding and student learning outcomes. However, the effectiveness of their use is highly dependent on real-world conditions, teacher readiness and competence, and support from the learning environment, such as supporting infrastructure.